Alstoscholactine and Alstolaxepine, Monoterpenoid Indole Alkaloids with γ-Lactone-Bridged Cycloheptane and Oxepane Moieties from Alstonia scholaris - Krishnan, Premanand; Lee, Fong Kai; Chong, Kam Weng; Mai, Chun Wai; Muhamad, Azira; Lim, Siew Huah; Low, Yun Yee; Ting, Kang Nee; Lim, Kuan Hon (American Chemical Society, 2018)
Two new monoterpenoid indole alkaloids, alstoscholactine (1) and alstolaxepine (2), were isolated from Alstonia scholaris. Compound 1 represents a rearranged stemmadenine alkaloid with an unprecedented C-6-C-19 connectivity, whereas compound 2 represents a 6,7-seco-angustilobine B-type alkaloid incorporating a rare γ-lactone-bridged oxepane ring system. Their structures and absolute configurations were determined by spectroscopic analyses. Compound 1 was successfully semisynthesized from 19E-vallesamine. Compound 2 induced marked vasorelaxation in rat isolated aortic rings precontracted with phenylephrine.